Resilience study of the tourism industry in Malioboro Yogyakarta - Al Muqsit, Faruq; Prihestiwi, Rosa Calista; Pramesti, Arinda Faradila; Pranata, Muhammad Deriel Ari (Proceeding International Conference on Accounting and Finance, 2024)
Malioboro Street is a pivotal point in disseminating Islam from the Yogyakarta Palace. Malioboro is interpreted as the journey to becoming a saintly figure (mali) and wandering (Oboro), encapsulating the concept of "sangkan paraning dumadi" or the human journey from birth to reunion with the god. Initially serving as a royal road, Malioboro progressively became a tourist attraction and an economic hub in Yogyakarta. Malioboro’s tourism and economic development significantly impacted its vicinity’s growth, manifesting in increased local incomes, employment opportunities, and enhanced community welfare. However, the pandemic Covid-19 disrupted its tourism landscape, impacting various sectors such as trade, transportation, and accommodation. An imperative research need emerged to investigate Malioboro’s tourism industry’s resilience regarding its impact resilience, particularly in the trade, transportation, and accommodation sectors. This research aims to investigate the strategies and approaches undertaken by these sectors in Malioboro to withstand the challenges posed by the pandemic. The research method is quantitative, with primary data collection methods, such as questionnaires and field observations, and secondary data collection from study literature. Data analysis comprises descriptive analysis and scoring to elucidate the resilience of Malioboro’s tourism industry. The findings suggest varied resilience across sectors, with trade, accommodation, and transportation having resilience in specific segments. The outcomes of this research will provide insights crucial for enhancing the resilience and sustainability of Malioboro’s tourism industry amid unprecedented challenges.